Opening of higher education? A lifelong learning perspective on the Bologna process - Anja P. Jakobi; Alessandra Rusconi (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2008)
Since 1999, European education ministers have discussed and further implemented the "Bologna process", a wide-ranging framework for the reform of higher education. Lifelong learning was added as a goal of the process in 2001. This article evaluates the extent to which the development of lifelong learning has progressed and examines whether the Bologna process has facilitated lifelong learning opportunities in a sample of countries. The evaluation of legislative instruments and policy positions of different stakeholders in Germany, France, Italy and the UK shows that countries link quite different strategies to lifelong learning in higher education. Specific national approaches exist which facilitate or restrict its development. Thus far, the impact of the Bologna process on this issue has been modest. The process has mainly had an impact on the discussion regarding lifelong learning, not necessarily whether and how such policies and programs are implemented. – – Im Jahr 1999 begannen die europäischen Bildungsminister mit dem "Bologna Prozess" eine weit reichende Hochschulreform. Als eines der Reformziele wurde 2001 "Lebenslanges Lernen" hinzugefügt. Dieser Beitrag untersucht anhand von vier Länderstudien (Deutschland, Frankreich, Italien und UK), inwiefern es gelungen ist, dieses Ziel umzusetzen und ob der Bologna Prozess neue Möglichkeiten lebenslangen Lernens an Hochschulen geschaffen hat. Dabei zeigt die Analyse von Gesetzen und Regularien, aber auch die Betrachtung politischer Positionen wichtiger Stakeholder, dass die einzelnen Länder sehr unterschiedliche Strategien mit lebenslangem Lernen an der Hochschule verbinden. Spezifische nationale Ansätze werden deutlich, die die Entwicklung dieses Ziels fördern oder behindern. Insgesamt wird deutlich, dass der Bologna Prozess vor allem die Diskussion um lebenslanges Lernen an der Hochschule gefördert hat, und nicht notwendigerweise, ob und wie dieses Ziel umgesetzt wird.
Keywords: 300; Hochschulreform; Lebenslanges Lernen; Hochschule; EU-Bildungspolitik; Deutschland; Frankreich